Single Parenting and Emotional Development of Primary School Students as Viewed by Nigerian Primary School Teachers - Adegboyega, Lateef Omotosho (Mimbar Sekolah Dasar, 2019)
This research investigated the influence of single parenting on emotional development of primary school students as viewed by Nigerian primary school teachers. A descriptive survey designed was adopted to draw 200 primary school teachers. One research question was raised and three null hypotheses were respectively postulated to guide the research at 0.05 level of significance. In addition, data analysis was done using t-test and Analysis of Variance (ANOVA). Furthermore, the findings revealed that low self-esteem was the most influencing emotional development of primary school students in Ilorin metropolis. The findings also revealed that there was no significant difference in the influence of single parenting on the emotional development of primary school students in terms of gender and qualification. It is recommended that teachers of students from single parents should be more sensitive to their emotional needs and always be ready to assist them. Moreover, counsellors should collaborate with teachers and parents to minimize the negative influence of single parenting. Teachers are suggested to be more sensitive and willing to assist students whenever they have problems at home. Single parents are suggested to provide more quality time with their children to avoid them performing negative behaviors. Parents are suggested to maintain stable home by living together to enhance their children emotional development.